DETERMINAN PEMANFAATAN PELAYANAN PUSKESMAS OLEH MASYARAKAT DI WILAYAH KERJA PUSKESMAS NAMORAMBE, KABUPATEN DELI SERDANG - Yunita Syahputi Damanik; Viktor Edyward Marbun; Rian Fedriko Ginting (Jurnal Penelitian Kesmasy, 2018)
Many factors cause the public health status in Indonesia is still low, including the community has not utilized health service facilities optimally, including the Namorambe Health Center is one of the health centers in Deli Serdang Namorambe Regency with the lowest number of visits and fluctuates every year from 2016-2018. . The type of research used is a survey with an explanatory research type to explain the influence of predisposing factors (knowledge, attitudes, and health beliefs), enabling factors (distance), and reinforcing factors (attitudes of health workers) towards the utilization of Community Health Centers in the working area of ​​the Namorambe Health Center, Namorambe District, Deli Serdang Regency in 2020. The population is all heads of families who live in the working area of ​​the Namorambe Health Center as many as 4,069 families. A sample of 93 families was taken using simple random sampling technique. Data were collected using a questionnaire and analyzed using a logistic regression test. The results showed that as many as 13 respondents (14.0%) used the Puskesmas and 80 respondents (86.0%) did not use the Namorambe Health Center. Based on the bivariate test in this study, it showed that the variables of knowledge (p = 0.001), attitude (p = 0.030) and health beliefs (p = 0.041) Namorambe Health Center, Deli Serdang Regency 2020. Suggestions are expected for employees and health workers at the puskesmas to improve and maintain good services to increase public perceptions of the available health service system.